Implementasi Software Hyperchem sebagai Media Praktikum Elektronik Visualisasi Struktur dan Sifat Senyawa Kimia di SMAN 1 Mawasangka Timur - Muhamad Jalil Baari; L A Na’ani; Agusriyadin Agusriyadin; Megawati Megawati; Faradisa Anindita; Alfiah Alif; Salim Salim; Netty Huzniati Andas; Arif Prasetya; Sarimuddin Sarimuddin; Dian Permana (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Chemistry is not merely a science that only studies theory in class. Chemistry learning requires practical or experimental activities to observe and directly apply chemical concepts during face-to-face meetings in class. Meanwhile, the unavailability of laboratory facilities is one of the factors in not carrying out chemistry practice. This causes students difficulties in understanding the concept of chemistry as a whole and can potentially reduce learning motivation. This public service activity aims to implement the Hyperchem software for teachers and students of SMA Negeri 1 Mawasangka Timur as an alternative solution for chemistry labs in the form of electronic labs. The chemical topics selected and considered suitable for this type of practice were the structure and properties of chemical compounds. This activity is carried out in the form of a workshop. Workshop materials use lectures, simulations, discussions, and question-and-answer models. The activity's results showed the workshop participants' enthusiasm to use the Hyperchem software as a chemistry lab media. This is reflected in the evaluation of the workshop implementation, which is carried out by assessing the response of the workshop participants based on indicators of relevance, the ability of the presenters, ease of use, availability, and usefulness of the Hyperchem software. The evaluation results show that the workshop and the implementation of the Hyperchem software as an electronic practice media for visualizing the structure and properties of chemical compounds received a positive response from the workshop participants.